Relaxed loading conditions for higher order homogenisation approaches (2011)
The present paper deals with the formulation of minimal loading conditions for the application of numerical homogenisation techniques, namely the FE methodology -- Based on the set of volume averaging rules connecting the heterogeneous micro and the homogeneous macro scale, the minimal constraints on the deformation of a micro volume are derived for a classical Cauchy as well as for a micromorphic overall continuum theory -- For both cases, numerical studies are included highlighting the main aspects of the proposed procedure